2018
DOI: 10.1111/bjdp.12263
|View full text |Cite
|
Sign up to set email alerts
|

Parental use of spatial language and gestures in early childhood

Abstract: Parents' use of spatial language and gestures is closely linked to children's spatial language development. Little is known about the quantity and quality of early spatial input and how infants' individual characteristics may be related to the spatial input they receive. Here, we examine (1) the amount and type of spatial input 16- to 21-month-old Turkish-learning children (n = 34) received in the context of a spatial activity (puzzle play) and (2) whether parental spatial input in the form of speech and gestu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
15
1
1
Order By: Relevance
“…Örneğin, aktif jest kullanan ve bu jestlerini sözel olarak ifade eden bir ebeveyn ile daha az jest kullanan ve kullanmış olduğu jestleri sözel olarak ifade etmeyen bir ebeveynin çocukların jest kullanımlarına farklı şekillerde katkı sağlayabileceği düşünülebilir. Tıpkı ebeveynin jest ve sözel ifadelerinin çocukların jest kullanımına etkisi olabileceği gibi çocukların daha önceki yıllarda kullanmış olduğu kelimeler de uzamsal dil kullanımı gibi belli alanlarda, ebeveynlerin şu anki kelime kullanımını etkileyebilir (Kısa, Aktan-Erciyes, Turan ve Göksun, 2019). Fakat ebeveynlerin bu süreçte oynadığı rolü ve çocuklarda bireysel farklılıklara olası etkisini anlamak için daha fazla çalışmaya ihtiyaç duyulmaktadır.…”
Section: Discussionunclassified
“…Örneğin, aktif jest kullanan ve bu jestlerini sözel olarak ifade eden bir ebeveyn ile daha az jest kullanan ve kullanmış olduğu jestleri sözel olarak ifade etmeyen bir ebeveynin çocukların jest kullanımlarına farklı şekillerde katkı sağlayabileceği düşünülebilir. Tıpkı ebeveynin jest ve sözel ifadelerinin çocukların jest kullanımına etkisi olabileceği gibi çocukların daha önceki yıllarda kullanmış olduğu kelimeler de uzamsal dil kullanımı gibi belli alanlarda, ebeveynlerin şu anki kelime kullanımını etkileyebilir (Kısa, Aktan-Erciyes, Turan ve Göksun, 2019). Fakat ebeveynlerin bu süreçte oynadığı rolü ve çocuklarda bireysel farklılıklara olası etkisini anlamak için daha fazla çalışmaya ihtiyaç duyulmaktadır.…”
Section: Discussionunclassified
“…At Time 2, we presented a wooden puzzle toy to parents and children to freely play for 3 min (see Kısa et al, 2019 for detailed information). The experimenter demonstrated how to play with the puzzle by fitting pieces into the wooden puzzle board, but no specific instructions were given.…”
Section: Methodsmentioning
confidence: 99%
“…During exploration, parents do not only utter object names but also supervise children's learning with other tools such as informative language or responsive behaviours (Tamis‐LeMonda et al, 2013). Parents also tune their spatial input based on their children's knowledge of spatial words (Kısa, Aktan‐Erciyes, Turan, & Göksun, 2019). Therefore, parental spatial input referring to object features can be related to object naming via tailoring visual and manual exploration for the shape‐based object categories.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the variability is due to children's characteristics, such as age, child language skills, and gender. In a recent study, Kisa et al reported that parental spatial language might vary as a function of age during toddlerhood and children's own spatial language comprehension assessed at an earlier age (Kisa et al, 2019). To sum, although gesture is tightly linked to spatial thinking, little is known about the role of parental spatial gestures in TB or PTB children's spatial development.…”
Section: Relations Of Parent and Child Spatial Language And Gesture To Child Spatial Developmentmentioning
confidence: 99%
“…Spatial words parents and children produced were also coded using an adapted version of the System for Analyzing Children's Language about Space (Cannon et al, 2007)-a manual for identifying and categorizing spatial words and phrases in English. Coding was modified based on prior work (Pruden et al, 2011;Kisa et al, 2019) examining the spatial language use in parents and children. We used six categories: (1) dimensional adjectives that describe the size of a person, place or thing (e.g., big, tall, little), (2) spatial feature terms that describe properties of nondimensional aspects of objects (e.g., bumpy, corner, flat), (3) positional and directional terms that describe the relative position of a person or thing in space (e.g., around, top, between), ( 4) shape terms that are used to label any 2D or 3D enclosed spaces (e.g., circle, sphere), ( 5) orientation and transformation terms that describe the relative orientation or transformation of objects in space (e.g., turn, rotate), and ( 6) continuous amount terms that describe the amount of continuous quantities (e.g., whole, half, part).…”
Section: Speechmentioning
confidence: 99%